Faktor-Faktor Kualitas Sumber Daya Manusia Terhadap Efektivitas Kerja Pegawai Pada Kantor Kelurahan Timbau Kecamatan Tenggarong - Suprayitno, Hero (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
The research result, Y = 2,849 + 0,629X1 + 0,111X2 + 0,255X3. The three independent variable which resulted positive symbol declare that every addition of 1 (one) independent variable unit will increase the dependent variable.R number which resulted is 0,602, means correlation or relation between education and training variable, leadership wisdom and job dicipline with the effectiveness of employees job is significant because number 0,602 is upper 0,5 or approach 1 ( r = 1 ). R square number is 0,36 means 36 % job effectiveness is influenced by education and training variable, leadership wisdom and job dicipline however the rest 64% is influenced by variable, such as compensation, work motivation, leader’s behaviour etc.Hypothesis experiment is known F table score is 2,72, means F arithmetic > F table or 2,75 > 2,72. So that the second hypothesis which is asked estimated together there is positive and significant effect between the quality of human resource factors to the effectiveness civil servant’s work at Kelurahan Timbau office can be received because the correctness has been proved.T experiment is known the three variable produce t arithmetic experiment > from t table experiment to the work effectiveness. According to the first hypothesis result which is asked, there is positive and significant effect between the quality of human resource factors to the effectiveness civil servant’s work at Kelurahan Timbau office can be received because the correctness has been proved. Key Word : Human resource , Effectiveness